Pitfalls and Challenges in the Interpretation of Rectal Cancer Magnetic Resonance Imaging - Abdul Haseeb Wani; Naseer A. Choh; Humairah M. Syed; Waris A. Mir; Rauf A. Wani; Irfan Robbani; Tahleel A. Shera (Journal of Gastrointestinal and Abdominal Radiology)
Magnetic resonance imaging (MRI) has taken a center stage in the imaging armamentarium of rectal cancer evaluation. Rectal cancer staging has undergone a paradigm shift from a surgico-pathological approach to a chemo-radiological one, helping effectively stratify patients for appropriate management. Primary lesion characterization, its morphology and internal characteristics, proximity of tumor to the mesorectal fascia, presence of extramural venous invasion, presence of extra mesorectal pelvic lymph nodes, and involvement of peritoneum and distant metastases are critical findings that impact patient management for which MRI is the preoperative gold standard. However, there are pitfalls, challenges, and misinterpretations related to technique, image quality, and knowledge gaps among the radiologists. These have major implications for patient management and their outcomes. In this article, we highlight the pitfalls and challenges in rectal cancer MRI and present practical solutions to circumvent these.